# SOLUTION: SOLVE for x: a) logbase3 x + logbase3 (x-8)=2 b) logbase4 (x+2)+logbase4(x-4)=2 c) logbase2 (5x-2)-logbase2 2 =1/2 logbase2 36 + 2 logbase2 3

Algebra ->  Algebra  -> Exponential-and-logarithmic-functions -> SOLUTION: SOLVE for x: a) logbase3 x + logbase3 (x-8)=2 b) logbase4 (x+2)+logbase4(x-4)=2 c) logbase2 (5x-2)-logbase2 2 =1/2 logbase2 36 + 2 logbase2 3       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Exponent and logarithm as functions of power Solvers Lessons Answers archive Quiz In Depth

 Question 185084: SOLVE for x: a) logbase3 x + logbase3 (x-8)=2 b) logbase4 (x+2)+logbase4(x-4)=2 c) logbase2 (5x-2)-logbase2 2 =1/2 logbase2 36 + 2 logbase2 3 Answer by edjones(7569)   (Show Source): You can put this solution on YOUR website!a) logbase3 x + logbase3 (x-8)=2 3^log[3]x * 3^log[3](x-8)=3^2 x(x-8)=9 x^2-8x-9=0 (x-9)(x+1)=0 x=9, x<>-1 because there is no log of a negative number. . b) logbase4 (x+2)+logbase4(x-4)=2 4^log[4](x+2) * 4^log[4](x-4)=4^2 (x+2)(x-4)=16 x^2-2x-8=16 x^2-2x-24=0 (x-6)(x+4)=0 x=6 . c) logbase2 (5x-2)-logbase2 2 =1/2 logbase2 36 + 2 logbase2 3 2^log[2](5x-2) / 2^log[2]2=2^log[2]6 * 2^log[2]9 explanation:{1/2 log 36= sqrt(36)} (5x-2)/2=6*9 5x-2=108 5x=110 x=22 . Ed